Evaluation of Pathology Results of Patients with a History of Breast Cancer who were Operated on for Gynecological Pathologies or Prophylaxis - Necim Yalcin; Isin Ureyen; Aysun Alci; Mustafa Gokkaya; Alper Kahraman; Gorker Sel; Gulsum Ekin Sari; Tayfun Toptaş (Gynecology Obstetrics & Reproductive Medicine)
Objectives: The present study aimed to evaluate the operation results of patients who were followed up due to breast cancer and were operated on due to gynecological pathologies or for prophylactic purposes, and determine the distribution of gynecological pathologies in breast cancer patients